Pengaruh Metode Belajar dan Kecemasan Diri terhadap Hasil Belajar Matematika Peserta Didik - Novi Marliani; Arif Rahman Hakim (Universitas Indraprasta PGRI, 2015)
The purpose of this study was to determine the effect of learning methods and anxiety on mathematics achievement. This research is quantitative research method used experiment method with two-way ANOVA analysis of the 60 samples. The sampling technique by means of simple random sampling or simple random samples taken randomly at one of Vocational Senior High School (SMK) in Depok. The results showed: (1) There are differences in mathematics achievement using the assignment (recitation) learning method and discussion learning methods, (2) There is a difference in students' mathematics achievement of anxiety low self-esteem and self-student high anxiety, (3) There isn’t interaction effect between learning method and anxiety on mathematics achievement.